Integrating Postcolonial Culture(s) into Primary English Language Teaching - Grit Alter (CLELEjournal, 2018)
This article argues in favour of using picturebooks to extend the limited view of cultural learning that is entailed in textbooks for teaching English at primary school. A critical view looking into textbooks for primary English education reveals that despite the general recognition of postcolonial literatures and cultures, target culture input almost only refers to the UK and the USA. Furthermore, the information students receive is over-generalising and stereotypical and does not pay tribute to the diversity of postcolonial cultures. This paper suggests that postcolonial literatures can be shared with primary English learners to broaden their perception of the English-speaking world. In view of the marginalized representation of these literatures and thus their respective cultures in ELT, this paper suggests closing the gap by using picturebooks from the Inuit and from Kenya and India. A comparison of two picturebooks from each geographical area reveals that one of these needs to be seen critically for its representation of cultural identity, whereas the other can be recommended for enhancing intercultural learning. As a conclusion, the article offers guiding questions of how to select postcolonial literature picturebooks to afford access to diverse cultures.